Use of an intravenous catheter to treat urinary distension in cases of feline lower urinary tract disease - Triyatjaya, Yoga; Hermawan, Firda Aisyah; Ratu Asyfa; Ratnaningsih, Tiara; Waskita, Pranyata Tangguh; Widianti, Ranny Indah (ARSHI Veterinary Letters, 2023)
Urolithiasis is a disease that commonly affects the urinary organs due to blockage of crystal stones in the urinary tract of male cats. A 3.5 year old male mixed breed domestic cat was examined at the Royal Purple Vet Clinic with complaints of a lack of appetite, fever, and vomiting. The results of the physical examination showed that the body temperature was 39.6°C, bladder distention occurred, and there was a pain response when palpated. Under emergency conditions, urinary distension was treated by insertion of an intravenous catheter (26G). Supporting examinations included urinalysis and microscopic examination of urine. Urinalysis results showed the presence of red blood cells, white blood cells, and protein in the urine. Meanwhile, the results of the microscopic examination showed that there were deposits of calcium oxalate crystal particles. The cat was diagnosed with urolithiasis with a Fausta prognosis. The treatment includes fluid therapy, antibiotics, anti-inflammatories, supplements, and herbal medicine. The cat experienced changes after being treated for four days, characterized by normal urination and no blood found in the urine